Lumbar paraspinal muscle transverse area and symmetry in dogs with and without degenerative lumbosacral stenosis. (27th August 2015) - Henderson, A. L.; Hecht, S.; Millis, D. L.
<x xml:space="preserve">Abstract</x> OBJECTIVES To investigate whether dogs with degenerative lumbosacral stenosis have decreased lumbar paraspinal muscle transverse area and symmetry compared with control dogs. MATERIALS AND METHODS Retrospective cross‐sectional study comparing muscles in transverse T2‐weighted magnetic resonance images for nine dogs with and nine dogs without degenerative ‐lumbosacral stenosis. Mean transverse area was measured for the lumbar multifidus and sacrocaudalis dorsalis lateralis muscles bilaterally and the L7 vertebral body at the level of the caudal endplate. Transverse areas of both muscle groups relative to L7 and asymmetry indices were compared between study populations using independent t tests. RESULTS Mean muscle‐to‐L7 transverse area ratios were significantly smaller in the degenerative lumbosacral stenosis group compared with those in the control group in both lumbar multifidus (0·84 ±0·26 versus 1·09 ±0·25; P=0·027) and sacrocaudalis dorsalis lateralis (0·5 ±0·15 versus 0·68 ±0·12; P=0·005) muscles. Mean asymmetry indices were higher for both muscles in the group with degenerative lumbosacral stenosis than in the control group, but highly variable and the difference was not statistically significant. CLINICAL SIGNIFICANCE These findings suggest that dogs with degenerative lumbosacral stenosis have decreased lumbar paraspinal muscle mass that may be a cause or consequence of the ‐syndrome. Understanding altered paraspinal muscle characteristics may improve understanding of the ‐pathophysiology and management options for degenerative lumbosacral stenosis.